Effects of Yoga on Depression and Anxiety in Patients with Musculoskeletal Disorders: A Systematic Review and Meta-Analysis - Uliyah, Musrifatul; Hidayat, Abdul Aziz Alimul; Aziz, Nahdah Aulia (Jurnal Keperawatan Muhammadiyah, 2025)
Background:Musculoskeletal disorders (MSDs) are a major cause of disability and are often accompanied by depression and anxiety, which may worsen pain and limit rehabilitation outcomes. Yoga, as a mind–body intervention, may provide both physical and psychological benefits; however, evidence regarding its effectiveness in MSD populations remains inconsistent. Methods:This systematic review and meta-analysis followed the PRISMA 2020 guidelines. Randomized controlled trials evaluating the effects of yoga on depression and/or anxiety in adults with musculoskeletal disorders were identified from PubMed/MEDLINE, Scopus, Cochrane Library, and CINAHL (January 2012–December 2025). A random-effects model was applied, and effect sizes were reported as mean differences or standardized mean differences with 95% confidence intervals. Risk of bias was assessed using the Cochrane Risk of Bias Tool. Results:Ten RCTs involving 1.063 participants were included. Yoga significantly improved depressive symptoms compared with control groups (MD = 1.19; 95% CI: 0.26–2.13; p = 0.01; I² = 61%) and significantly reduced anxiety (MD = 4.09; 95% CI: 0.64–7.54; p = 0.02; I² = 96%). Overall study quality ranged from low to moderate, mainly due to limited blinding. Conclusions:Yoga is associated with significant reductions in depression and anxiety among patients with musculoskeletal disorders. Despite substantial heterogeneity, yoga may be considered a complementary intervention within holistic musculoskeletal rehabilitation. Further high-quality trials with standardized protocols are required.